2002
DOI: 10.1046/j.1365-2249.2002.01837.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CD14 promoter polymorphism andH. pyloriinfection and its clinical outcomes on circulating CD14

Abstract: SUMMARYCD14 is a pattern recognition receptor on the membranes of monocytes and macrophages for several microbial products, of which lipopolysaccharide (LPS) is the best known. A shed form of CD14 is present in serum. As the CD14 gene promoter polymorphism -159C/T and some bacterial infections may affect the sCD14 levels, we compared the impact of both the CD14 promoter polymorphism and Helicobacter pylori infection on serum sCD14 levels in 201 dyspeptic patients (group 1) who had undergone gastroscopy, and 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
1
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 43 publications
(44 reference statements)
3
66
1
6
Order By: Relevance
“…It was reported in a previous study that elevated sCD14 levels were associated with H. pylori infection, especially in subjects with the CD14 CC genotype (29). In the present study, we did not observe any significant elevation of sCD14 in subjects with H. pylori versus those without H. pylori, or in subjects with the CD14 À260CT or TT genotype versus those with the CC genotype either in cases and controls, although a nonsignificantly higher mean value of sCD14 was observed in subjects with the CC genotype and H. pylori infection.…”
Section: Discussionmentioning
confidence: 83%
“…It was reported in a previous study that elevated sCD14 levels were associated with H. pylori infection, especially in subjects with the CD14 CC genotype (29). In the present study, we did not observe any significant elevation of sCD14 in subjects with H. pylori versus those without H. pylori, or in subjects with the CD14 À260CT or TT genotype versus those with the CC genotype either in cases and controls, although a nonsignificantly higher mean value of sCD14 was observed in subjects with the CC genotype and H. pylori infection.…”
Section: Discussionmentioning
confidence: 83%
“…The distribution of CC genotype in Taiwan is significantly low as compared with those in Western countries. 9,15,16 The mean fluorescence intensity (MFI) of mCD14 on PBMC and plasma levels of sCD14 were measured in 84 healthy individuals (age 20-45 years; mean7s.d., 23.874.3 years; 44 females and 40 males). As shown in Figure 1, mCD14 in TT genotypes (mean: 1818) are significantly higher than those in CT (mean: 1517; P ¼ 0.044) and CC (mean: 1603; P ¼ 0.034) genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the severity of atrophic gastritis induced by longterm infection of Haemobartonella felis in CH3/He mice is significantly higher than that in LPS-nonresponder CH3/HeJ mice (47), which have an inactivating point mutation in Tlr4 (48). More recently, Karhukorpi et al (49) reported elevated serum levels of a soluble form of the CD14 molecule in Haemobartonella pyloriinfected individuals. Soluble CD14 binds to LPS and facilitates its signaling, and this study has shown that CD14 promoter polymorphism is associated with the disease outcome.…”
Section: Discussionmentioning
confidence: 99%